Hybrid nanoparticle platforms toward multifunctional surface-enhanced Raman scattering (SERS) spectroscopy applications - Koh, Charlynn Sher Lin (Nanyang Technological University, 2020)
Surface-enhanced Raman scattering (SERS) spectroscopy is a highly sensitive spectroscopy technique that can boost the Raman fingerprint signals of molecules. However current SERS applications are limited to dye/thiolated molecules sensing or monitoring spontaneous reactions, mainly due to poor analyte-plasmonic surface affinities. In this thesis, we address these challenges by designing hybrid plasmonic platforms for multifunctional SERS applications. In chapter 2, we demonstrate the fabrication of hybrid SERS- and electrochemically-active three-dimensional plasmonic liquid marble for in-situ monitoring of an electrochemical redox reaction. In chapter 3, we incorporate metal-organic frameworks (MOFs) with Ag nanocubes superlattice array to preconcentrate non-adsorbing vapor molecules for SERS detection. For chapter 4 and 5, we exploit plasmonic nanoparticles-MOF hybrids for gas-based applications, realizing catalysis and SERS investigation of interfacial processes for ambient electrochemical nitrogen reduction and CO2 carboxylation reaction, respectively. Lastly, I conclude my thesis with a summary of my research works and identify potential future work.